Interest and Text Anxiety as Correlate of Secondary School Students’ Academic Achievement in Chemistry in Ogidi Education Zone - Regina Ijeamasi Enebechi; Ngozi Nonye Achufusi; Anene Anna Okwuchukwu (Sean Institute, 2026)
The study examines interest and test anxiety as correlates of secondary school students’ academic achievement in chemistry in Ogidi Education Zone. Two research questions guided the study and two null hypotheses were tested at 0.05 level of significance. A correlational research design was adopted for the study. The population of the study consisted of all the 1,754 senior secondary school two (SS2) chemistry students in the 40 public secondary school in Ogidi education zone in Anambra state. 375 SS 2 chemistry students were sampled using multi-stage sampling procedures. Chemistry Interest Scale (CIS), Chemistry Text Anxiety Assessment inventory (CTAAI) and the 2023/2024 SS2 cumulative examination results in Chemistry were used for data collection. The instruments were validated. The reliability of the instruments was established using Cronbach Alpha with coefficients of 0.87 for CIS and 0.83 for CTAAI. Pearson Product Moment Correlation was employed for analysis of the data collected using Statistical Package for Social Sciences (SPSS, version 25). The findings of the study showed a moderate positive relationship (r = 0.413) between interest scores and academic achievement scores of secondary school students in Chemistry. It equally revealed that the relationship between test anxiety scores and academic achievement scores of secondary school students in Chemistry in Ogidi Education Zone is a moderate negative relationship (r= -0.513). This means that students with higher test anxiety tend to perform less well academically in Chemistry, while students with lower test anxiety generally perform better. Based on the findings it was recommended amongst others that teachers should incorporate student-centered instructional methods, such as inquiry-based learning, problem-solving approaches, and hands-on laboratory activities, to spark students' interest in Chemistry. Schools should organize workshops and training sessions aimed at helping students manage test anxiety. Techniques such as mindfulness, relaxation exercises, and effective study habits should be taught to equip students with skills to handle the pressure of assessments and examinations effectively